The Development of Grade 8 Student Analytical Thinking and Learning Achievement Using the Integrated Problem-Based Learning and Think-Pair-Share Technique - Pitchayakorn Theabthueng,; Jatuporn Khamsong,; Wittaya Worapun, (Journal of Educational Issues, 2024)
The purposes of the current study include (1) to examine the effect of integrated problem-based learning and Think-Pair-Share technique on the development of grade 8 students’ analytical thinking and (2) to examine the effect of integrated problem-based learning and Think-Pair-Share technique on the development of grade 8 students’ science learning achievement. The participants were 42 students in a school in Thailand. The purposive sampling method was employed. The instruments include a learning management plan of force and movement, analytical thinking test, and a learning achievement test. The data were analyzed using percentages, mean scores, standard deviation, and a paired samples t-test. The results of the study could be concluded that the integration of problem-based learning and Think-Pair-Share collaborative learning strategies was beneficial in both developing processes of thinking and improving students’ knowledge of class contents. The results of the study could also illustrate how learners gained benefits from the integrated methods and imply how they should be useful in the pedagogical and academic setting.